2014
DOI: 10.1007/s11164-014-1802-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pelargonium extract and oil as eco-friendly corrosion inhibitor for steel in acidic chloride solutions and pharmacological properties

Abstract: International audienceThere is a growing trend in utilizing plant extracts and pharmaceutical compounds as corrosion inhibitors. Accurate identification of the essential oil of aerial parts of Pelargonium was obtained using hydrodistillation, gas chromatography and gas chromatography–mass spectrometry. The oil was predominated by citronellol (22.8 %). The inhibitory effect of essential oil and extract of Pelargonium was estimated on the corrosion of mild steel in 1 M hydrochloric acid (HCl) using weight loss, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…1a). Several scientists in their studies (Table 3) reported similar results [2,4,6,[15][16][17][18][19], which confirm that the SSE act as effective inhibitors. The evolution in inhibition efficiency may be attributed to the adsorption of the particles at the carbon steel (X52) surfaces [20].…”
Section: Weight Loss Measurementsmentioning
confidence: 58%
“…1a). Several scientists in their studies (Table 3) reported similar results [2,4,6,[15][16][17][18][19], which confirm that the SSE act as effective inhibitors. The evolution in inhibition efficiency may be attributed to the adsorption of the particles at the carbon steel (X52) surfaces [20].…”
Section: Weight Loss Measurementsmentioning
confidence: 58%
“…The gravimetric method (weight loss) is known to be the most widely used method of monitoring inhibition efficiency [9]. The mild steel specimens of dimension 1×1×0.1 cm were used in these studies.…”
Section: Weight Loss Measurementsmentioning
confidence: 99%
“…For several years, the interest of our team, is the valorization of natural products from aromatic and medicinal plants, using them as natural antioxidants [10][11][12] and ecofriendly corrosion inhibitors [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%